Two new species of Cyphocharax (Teleostei: Characiformes: Curimatidae) from headwaters of the Jequitinhonha and São Francisco river basins, Minas Gerais, Brazil - Dutra, Guilherme Moreira; Penido, Iago De Souza; Mello, Gabriel Caetano Guimarães De; Pessali, Tiago Casarim (Zootaxa, 2016)
Two new species of Cyphocharax from southeastern Brazil are described. Both new species share with C. punctatus, and C. vanderi the presence of a midlateral series of irregular patches of dark pigmentation along the lateral line. Cyphocharax jagunco, new species, from Rio Jequitinhonha basin, is distinguished from C. lundi, C. punctatus, and C. vanderi by the number of patches of dark pigmentation along lateral line; the number of pored scales posterior to the hypural joint; the number of scales in the lateral line; and the number of scales rows above lateral line. Cyphocharax lundi, new species, from Rio São Francisco basin, is distinguished from C. jagunco, C. punctatus, and C. vanderi by the presence of dark spots above the lateral line; and the number of scales in the lateral line. Comments on the relationships of the new species within Cyphocharax are presented.